PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI MEDIA SEDHAN (SEDOTAN PENJUMLAHAN) MATEMATIKA MATERI PENJUMLAHAN KELAS II SDN SIDOTOPO IV/51 - Ahmad Zadid Taqwa; Vicky Dwi Wicaksono; Sulistyowati; Sarwenda Budi Pratiwi; Siti Azizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was carried out to improve student learning outcomes in mathematics subject matter of addition using the addition straw media. The hypothesis of this research is that the use of addition straw media can improve student learning outcomes in mathematics subjects for class II students at SDN Sidotopo IV 51 Surabaya. This research is classroom action research which goes through 4 stages, namely planning, implementation, observation and meetings. The subjects of this research were class II students, totaling 27 students. The data collection techniques used are tests and non-tests. Non-tests include observation, interviews, and documentation. The data analysis techniques used are quantitative and qualitative. The research results show that student learning outcomes after using the adding straw media have a good impact on student learning outcomes. This is proven by the increase in completeness in each cycle starting from pre-cycle to cycle 2. In cycle 1 the average classical completeness was only 60.62% with the number of students who completed it being 12 students and 15 students not yet completed, then in cycle 2 the average Classical completion rose to 80% with the number of students who completed it being 24 students and 3 students who had not yet completed it. Learning success can be determined by several factors, including the teacher. Teachers have a very important role, namely as implementers of the curriculum and delivery of teaching materials or materials. Teachers have abilities in the learning process that are very closely related to their teaching abilities. The teacher's role in the learning process includes, among others, as a communicator/informator, conductor, organizer, motivator, and educator. In a teaching and learning process as a whole the role of the teacher cannot be ignored.